PEMBERDAYAAN KELOMPOK TANI SUMBER MAKMUR DALAM MENGOLAH LIMBAH BIJI ALPUKAT MENJADI KOPI BUBUK HERBAL - Ainol Ainol; Ummi Nadziratul Laily; Lailatul Hasanah; Laeylatul Karomah; Intan Maghfirah; Rosita Rosita; Diana Sarkila; Fitria Ida Maulida (LP2M Universitas Ibrahimy, 2023)
Avocado fruit is one type of fruit that contains fat, vitamins A, B, C and E and carotene. Increased consumption of avocado fruit causes an increase in the production of avocado seed waste. This waste can be innovated into a healthy ground coffee drink. Community empowerment in utilizing avocado seed waste is carried out through several stages in the ABCD (Asset Based Community-driven Development) approach including inculturation, discovery, design, define, and reflection. This activity was carried out with the Sumber Makmur Farmer Group in Ranuagung Village, Tiris District. This research aims to empower the community and farmer groups by utilizing waste avocado seeds to make herbal ground coffee. In addition, the community can find an asset in the form of an avocado seed which was originally thought of as a pile of trash, which has become an asset that provides economic value. Utilization of avocado seed waste can also improve environmental cleanliness in Ranuagung Village.